THE DEVELOPMENT OF CARIYĀPIṬAKA-BASED DRAWING AND COLORING BOOKS FOR EARLY CHILDHOOD EDUCATION STUDENTS - Setiawan, Panna; Widiyono, Widiyono; Parsiyono, Parsiyono (Jurnal Pencerahan, 2023)
Research on the development of Cariyāpiṭaka-based drawing and coloring books as teaching materials for early childhood education students level B students at Vidyananda and Vidya Dhamma Kindergartens was carried out because there are still very few learning resources for early childhood education programs (PAUD) and Kindergarten aged children based on Buddhist stories. The type of research used by researchers is research and development with the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. Data collection techniques used by researchers include observation, interviews, questionnaires and documentation. Data credibility is assessed by transferability, dependability, and confirmability. The data analysis techniques used for qualitative data are reduction, presentation and drawing conclusions. Meanwhile, quantitative data was analyzed using descriptive percentage theory. Based on the results of feasibility research from experts, the Cariyāpiṭaka-based Drawing and Coloring book received a feasibility percentage of 86.1% from material experts, 85.62% from media experts, and 89.95% for effectiveness. Apart from that, the students' response was very enthusiastic about the Cariyāpiṭaka-based drawing and coloring book. Based on the results of the percentage of response assessments from test subjects, it can be said that the Cariyāpiṭaka-based Drawing and Coloring book is very suitable as teaching material for Level B PAUD students at Vidyananda and Vidya Dharma Kindergartens. Moral messages contained in the story (1) Ruru Raja Deer, this wise Deer has a moral message of not breaking promises, (2) This wise Bull King has a moral message of practicing patience.